Estudio de prefactibilidad para la instalación de una empresa de producción de champú de coco (Cocos nucifera) en barra - Chichizola Chaves, Andrea (2020)
In the present pre-feasibility study, the viability of the implementation of a coconut shampoo bar production workshop was determined. During the market study for our product we determined qualitatively (using criteria of segmentation) and quantitatively the target population, which belongs to NSE A, B and C of Lima Metropolitana. In addition, surveys were designed and implemented to calculate the demand of the project, which was projected for the years 2020 to 2024, obtaining 32 403 bars of shampoo in the last year. In addition, an analysis of the current shampoo market offer was made, and the price was set at 39.90 soles for each shampoo bar. For the localization, the macro location analysis got Lima Sur as the winning sector, and subsequently Chorrillos won as the district where the production workshop will be located. The size of the factory was established using the market size criteria as the decisive factor, obtaining the result of 32 403 bars of shampoo per year. Additionally, this result exceeds the equilibrium point. Later on, the production process stages were established, and, consequently, the capacity installed in the factory. The bottle neck of the production process is the stage of packaging and sealing, which has an annual production capacity of 185 220 bars of shampoo. Regarding the layout of the installations, the minimum space for the production area is 26 m2, and the total area will be 290 m2. For the economic and financial evaluation, the total investment required will be 258 613 soles. The most profitable option would be to finance 35% of the total investment through a bank loan, thus obtaining a NPV of 223 309 soles (IRR of 48%, B/C ratio of 2.33 and recovery period of 3.99 years). Finally, the added value generated by the project would be 2 463 115 soles, which indicates that the project is extremely beneficial for the society.